Symposium on Spatial User Interaction 2020
DOI: 10.1145/3385959.3418453
|View full text |Cite
|
Sign up to set email alerts
|

Mission Impossible Spaces: Using Challenge-Based Distractors to Reduce Noticeability of Self-Overlapping Virtual Architecture

Abstract: Impossible spaces make it possible to maximize the area of virtual environments that can be explored on foot through self-overlapping virtual architecture. This paper details a study exploring how users' ability to detect overlapping virtual architecture is affected when the virtual environment includes distractors that impose additional cognitive load by challenging the users. The results indicate that such distractors both increase self-reported task load and reduce users' ability to reliably detect overlaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Other studies attempted to explore how the size and layout of physical tracked space influence the performance of redirected walking controllers [3,31]. In terms of visual perception in VR, previous studies stated users' tend to underestimate virtual walking speeds [2,6,10,11] and the presence of distractors in VEs bias the threshold range to be larger [14,15,17,48]. While Nguyen et al [34] reported that a room's dimension does not significantly affect curvature gain thresholds, Kim et al [24] stated that relative translation gain thresholds differ according to the VE size and referred to Messing et al [30] in assuming that this may be induced by the location of the virtual horizon.…”
Section: Threshold Estimation and Perceptionmentioning
confidence: 99%
“…Other studies attempted to explore how the size and layout of physical tracked space influence the performance of redirected walking controllers [3,31]. In terms of visual perception in VR, previous studies stated users' tend to underestimate virtual walking speeds [2,6,10,11] and the presence of distractors in VEs bias the threshold range to be larger [14,15,17,48]. While Nguyen et al [34] reported that a room's dimension does not significantly affect curvature gain thresholds, Kim et al [24] stated that relative translation gain thresholds differ according to the VE size and referred to Messing et al [30] in assuming that this may be induced by the location of the virtual horizon.…”
Section: Threshold Estimation and Perceptionmentioning
confidence: 99%
“…However, it also seems possible that environmental manipulations can be performed inside users' FOV, when visual attention is not focused on the manipulated object [29], or by masking the manipulation using blinks and saccades, as has been done in relation to hand remapping [53]. On the topic of masking, previous work on redirected walking indicates that both passive [35] and active [15] distractors can be used to mask warping of users' movements; and challenge-based distractors, imposing additional cognitive load, may make users less like to notice manipulations of virtual architecture [12]. Thus, it seems relevant for future work to explore how interaction and distraction can be used to mask both body warping and change blindness remapping.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Moreover, it is influenced by events occurring in virtual reality space. For example, when performing other tasks while walking, the user's attention was distributed to the task performance, making them less sensitive to changes in their speed (Ciumedean et al, 2020, Gao et al, 2020.…”
Section: Cognitive Threshold and Visual Perceptionmentioning
confidence: 99%